Experiences of Mothers with Invisible Illnesses - Koivisto, Jami (My University, 2018)
With research lacking in the area of mothers coping with invisible, chronic illnesses, this research explored the obstacles that mothers may face with an invisible illness, and how this may affect the everyday lives of these women. Issues that were faced included delegitimization of illness, self-doubt, caregiver fatigue, and mother guilt. Relations to the societal of expectations of mothers, what constitutes an illness, and women’s health, are explored as well as topics for future research.
Keywords: Mother Guilt; Delegitimization; Invisible Illness; Dysautonomia; Communicating Arts